China's ongoing agricultural reform - Carter, Colin A.; Zhong, Fu-Ning; Cai, Fang (1990 Institute, 1996)
The authors conclude with suggestions for fundamental changes in China's agricultural policy that are needed if the nation is to feed its 1.2 billion people